Numerical Research of Lightweight Foam Concrete Replacement Method of Deep Soft Foundation Treatment of Low-Filled Embankment - Fanfan Li; Zhifeng Zhang; Xing Chen; Zecheng Chi; Jianbin Li; Wei Wang (Geofluids)
A new method of replacing soft soil with lightweight foam concrete (lightweight foam concrete replacement method, LFCRM) is carried out to treat deep soft foundation under the low-filled embankment. Two-dimensional models with different thicknesses of replacement are established by the finite element platform (MIDAS/GTS). Moreover, the deformation and stress distribution law of treated foundation is analyzed by numerical simulation with different models. The results are as follows: (1) LFCRM can offset part of dead load; (2) the transverse distribution of settlement presents an “arc” shape; (3) the replacement made of lightweight foam concrete can spread stress well; (4) increase of replacement thickness will cause the necking of the additional stress “bubble”; (5) initial excess pore water pressure is related to the additional stress, and its dissipation path is deduced; (6) preliminary analysis indicates the feasibility of LFCRM for treating deep soft foundation with the low-filled embankment.